Optical elastography: tracking surface waves with digital image correlation. (25th February 2019) - Zorgani, Ali; Ghafour, Tarek Abdul; Lescanne, Maxime; Catheline, Stefan; Bel-Brunon, Aline
Abstract: Elastography consists in evaluating the propagation speed of waves into a tissue to estimate its stiffness. Usually this method is based on Ultrasounds, magnetic resonance imaging or optical coherent tomography. This paper proposes a simple optic method using ultrafast cameras. Based on digital image correlation (DIC), the tracking of elastic surface wave from white light intensity pattern, allows estimating the propagation speed as an indicator of the tissue local stiffness. Two configurations are presented: (1) 2D imaging of a flat phantom surface with a single camera and (2) 3D imaging of a curved phantom surface with two cameras. As a feasibility study of the first configuration, surface wave speed was measured on isotropic and anisotropic phantoms. Comparisons with ultrasound methods fully validate this approach. Although more sophisticated, the second configuration account for propagation distortions caused by locally curved topology. Triangulation techniques used to retrieve local topology are named stereo-correlation in the field of biomechanics. Stereo-elastography is thus proposed to determine tissue local elasticity from any soft tissue surface wave.